Capital Flows to the New World as an Intergenerational Transfer - Taylor, Alan M.; Williamson, Jeffrey G. (Journal of Political Economy, 1994)
The late nineteenth century saw international mass migrations of capital and labor from the Old World to the New. Factors chased each other and the abundant resources at the frontier. Demographic structure also contributed to the massive capital flows from Britain to the New World. The dependency hypothesis is confirmed by estimation of savings functions in three New World economies (Argentina, Australia, and Canada) in which high dependency rates may have significantly depressed domestic savings rates and pulled in foreign investment: in effect an intergenerational transfer from old savers in the Old World to young savers in the New.